Hepatic arterial infusion chemotherapy combined with PD-1 inhibitors and tyrosine kinase inhibitors for unresectable hepatocellular carcinoma: A tertiary medical center experience - Luo, Laihui; Xiao, Yongqiang; Zhu, Guoqing; Huang, Aihong; Song, Shengjiang; Wang, Tao; Ge, Xian; Xie, Jin; Deng, Wei; Hu, Zhigao; Wen, Wu; Mei, Haoran; et al. (Frontiers in Oncology, 2022)
Background: Unresectable HCC (uHCC) still accounts for the majority of newly diagnosed HCC with poor prognosis. In the era of systemic therapy, combination therapy with tyrosine kinase inhibitors (TKIs) and programmed cell death protein-1 (PD-1) inhibitors has become mainstream. Hepatic artery infusion chemotherapy (HAIC) as a local treatment has also shown a strong anti-tumor effect. This study aimed to investigated the efficacy and safety of TKIs, PD-1 inhibitors, plus HAIC for unresectable hepatocellular carcinoma. Methods: This retrospective study included patients with initially unresectable HCC between October 2020 to April 2022 who had received at least one cycle of therapy with TKIs, PD-1 inhibitors, plus HAIC. The primary outcome included overall response rate (ORR), the disease control rate (DCR), surgical conversion rate, progression-free survival (PFS) and treatment-related adverse events. Results: A total of 145 patients were included in the study. The median cycle of HAIC and PD-1 were 3 and 4, respectively. The best ORR was 57.2% (83/145), 9 had achieved complete response (CR), DCR was 89.7% (130/145), according to the modified RECIST criteria. Median time to achieve CR or PR was 65 days. Surgical conversion rate was 18.6% (27/145), seven patients (7/27,25.9%) achieved pathological complete response (pCR). The median follow-up was 12.5 months (4.5-20 months), and the median PFS was 9.7 months. Subgroup analysis showed that Child-pugh A patients had higher DCR (92.2% vs 79.3%, P=0.041) than Child-pugh B patients, as well as increased successful conversion rate (22.4% vs 3.4%, P=0.019). Patients without vascular invasion and extrahepatic metastases showed higher PR (63.4% vs 43.3%, P<0.05) and ORR (73.2% vs 50.0%, P<0.05) than those with vascular invasion. The ORR (73.2% vs 45.5%, P<0.05) and DCR (95.1% vs 78.8%, P<0.05) were also significantly better than those of patients with extrahepatic metastases. HAIC regimen was not related to efficacy (All P>0.05. The incidence rate of grade 3/4 treatment-related adverse events was 17.7% without fatal events. Conclusion: The triple combination therapy of HAIC and TKIs plus ICIs for patients with initially unresectable HCC exhibited satisfactory efficacy with tolerable toxicity.